Báo cáo Tổng hợp ý kiến của các vị đại biểu Quốc hội thảo luận tại Tổ về dự án Luật Dữ liệu - Tổng thư ký Quốc hội (2024)
Toàn văn Báo cáo Tổng hợp ý kiến của các vị đại biểu Quốc hội thảo luận tại Tổ về dự án Luật Dữ liệu.